An analysis of translation techniques used to translate metaphors and similes in Eka Kurniawan’s Cantik Itu Luka into Beauty Is a Wound - Agni Kusti Kinasih (Jurnal Linguistik Terapan, 2016)
This study is a descriptive qualitative research implemented in the area of translation studies. It aimed to identify the translation techniques used in translating metaphors and similes in the national best-selling novel Cantik itu Luka authored by Eka Kurniawan (2015) into Beauty is a Wound translated by Anne Tucker. Purposive sampling was chosen to adjust to the researcher’s limitation and feasibility, where Chapter I of the two novels was selected as the source data. In translating similes and metaphors as figurative language, a translator must be able to maintain the imaginative pleasure, imagery, and emotional intensity without eliminating the exact meaning. This study employed two stages of analysis namely domain and taxonomic analyses. In the domain analysis, similes and metaphors from the two novels were identified, reviewed, and checked whether they had fulfilled the criteria of metaphors and similes covering topic, image, point of similarity, and nonfigurative equivalent. In performing the taxonomic analysis, the 18 translation techniques namely adaptation, amplification, borrowing, calque, compensation, description, discursive creation, established equivalent, generalization, linguistic amplification, linguistic compression, literal translation, modulation, particularization, reduction, substitution, transposition, and variation proposed by Molina & Albir (2002) used to translate the selected metaphors and similes were identified and discussed. Based on the analysis result, modulation and literal translation were the most frequently used techniques. Modulation was applied 14 times (19.44%), while literal translation was applied 15 times (20.83%) in the single technique. Meanwhile, in the double technique, modulation was the most frequently used one with 7-time occurrence (9.72%). In the triple technique, modulation was also the most frequently used one with 2-time occurrence (2.78%).